World Bank East Asia and Pacific Economic Update, October 2016 : Reducing Vulnerabilities - World Bank (Washington, DC: World Bank, 2016)
Growth in developing East Asia Pacific (EAP) has remained broadly stable in the past 6 months. It is expected to decline gradually during 2016-18, driven entirely by the ongoing slowdown in China, partly offset by a pick-up in the large ASEAN economies.